A novel monitoring scheme to detect iron oxide particle deposits on the internal surface of PVC drinking water pipes. Issue 11 (6th October 2021) - Braga, Artur Sass; Filion, Yves
Abstract : PVC pipe wall samples were acquired from a full-scale drinking water distribution laboratory using 3D printed coupons. Brightfield microscopy and imaging processing were used to investigate iron oxide particles deposited on samples surface. Abstract : The internal surface of drinking water pipes is often populated with particulate iron oxide deposits that originate from the corrosion of old system components. These sediment deposits may assist in the growth of biofilms and may contribute to the deterioration of drinking water quality between the point of treatment and consumption. In this context, approaches to capture sediment and biofilm samples from the pipe wall offer the potential to perform the detailed examination of material accumulation and mobilization processes. The aim of this paper was to present a novel monitoring scheme to investigate the accumulation and mobilization of iron oxides particles on the internal wall surface of PVC pipes. An improved coupon sample technology, based on 3D printing, was developed to overcome several shortcomings reported with previous coupon systems. Controlled laboratory experiments were realized by inoculating a full-scale drinking water distribution system with iron oxides particles to simulate the contamination and mobilization of sediments from the pipe wall. A novel automated brightfield microscopy approach was used to produce direct microscopic observations of the iron oxides particles on the internal surface of PVC pipes collected with the new coupons. An imaging post-processing algorithm was used to analyze the percent sediment coverage and the particle size distribution on the coupon at different stages of the experiment. Results showed that fine particles progressively accumulated in the inverts of pipes and particles with diameter larger than 5 μm were easily mobilized by flushing operations. The new insights about the accumulation and mobilization of particles demonstrates the potential of the new scheme to assist water utilities on the monitoring of operational drinking water distribution networks.